Identitetsdannelse i de første kristne menigheder - Birgitte Graakjær Hjort (Religionsvidenskabeligt Tidsskrift, 2002)
The forming of social identity is a process by which the common identifications of an ingroup, which provide members with a sense of belongingness, are being compared with and differentiated from relevant outgroups. Theories within social anthropology and group psychology contribute to explain this process and the functions of its complex interplay between similarities and differences. The making of comparisons  becomes a competitive act of differentiation, the purpose of which is to achieve or maintain values of the ingroup that are held superior to those of the relevant outgroups. The dispute of the letter to the Galatians is an example of the process and its social competition strategy.